Pelatihan Penggunaan Aplikasi Mobile Pajak untuk Kelompok Ternak Itik “Manunggal Lestari” di Desa Duwet Kecamatan Wates Kabupaten Kediri - Riningsih, Duwi; P., Andy Chandra; Eferyn, Krissantina; P., Oktaviani Wahyu; Yunanto, Ferdy (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
The "Manunggal Lestari" Duck Farming Group was established in 2010 but is still on a small scale and the number of members is limited, and then the number of members increases and the turnover generated from duck farming is also large. The “Manunggal Lestari” Duck Breeders Group, most of its members have not fulfilled their tax . Most of them said that because they did not know or were blind to the science of taxation, they did not know how the process of calculating taxes, paying taxes and reporting taxes. The method used for this research was descriptive qualitative by explaining the ease of fulfilling tax obligations with Mobile Tax. the result of this service is that duck breeders are able to operate Mobile Tax in carrying out their tax.